THE INFLUENCE OF SERVICE QUALITY AND PERCEIVED VALUE ON CUSTOMER SATISFACTION: A STUDY OF GACOAN NOODLES BUAH BATU, BANDUNG - Rammelbergi, Janadi; Naysa, Kayla Nazwa; Susanti, Femy; Rohmah, Yunia Nur; Susilawati Sugiana, Neng Susi (Jurnal Komputer Bisnis, 2025)
This study aims to explore the relationship between perceived value and service quality and customer satisfaction at Gacoan Buah Batu, Bandung. Understanding the primary factors that influence consumer happiness has become essential for the viability of businesses in the food and beverage sector as competition heats up. This study's main goal is to find out how consumers' opinions about the value and quality of the services they receive affect their entire eating experience and level of satisfaction. Fifteen respondents who frequently shop at Gacoan were interviewed in-depth as part of a qualitative research technique. To find recurrent trends and insights, the data underwent thematic analysis. The results show that clients value cleanliness, perceived pricing, staff response, and timeliness of service highly. When these elements meet or exceed expectations, customer satisfaction significantly increases. Conversely, inconsistencies in service or perceived decline in value lead to dissatisfaction. A notable uniqueness of this study lies in its focus on a single outlet, providing a micro-level understanding of consumer behavior in a specific urban setting. The practical implication of this study suggests that Gacoan can enhance customer loyalty by maintaining consistent service quality and optimizing value perception through promotions or personalized experiences. Businesses in similar markets may also benefit from adopting a localized approach to understanding customer needs. These insights serve as a valuable reference for improving service management strategies in Indonesia’s competitive culinary sector.